Developing future skills in teacher education: Insights from Omani pre-service teachers - Eid, Mahmoud; Al-Senaidi, Said (Journal of Interdisciplinary Studies in Education, 2025)
This study uses a quantitative methodology, employing a structured questionnaire, to examine the effectiveness of courses offered by Rustaq College of Education in enhancing students’ future skills. The study focuses on pre-service teachers’ perceptions within the context of the Omani Future Skills Paradigm Framework. A total of 128 students from different disciplines (English, Mathematics, Science) participated in the study survey. The study results show that these courses play a critical role in developing essential competencies, particularly in embracing diversity and open-mindedness in both academic and professional environments. The study also identifies areas for improvement, including the need for ongoing development, the use of non-traditional problem-solving strategies, the presentation of diverse perspectives, and clearer problem articulation. The study findings reveal differences in responses based on factors such as students’ major, gender, and academic year. Conducted during the fall 2023 semester, this study provides insights that could improve teacher education by prioritizing future skills and informing professional development programs for teachers.